Association of lipid profile with ischemic stroke - Uddin, Md Jalal; Alam, B; Jabbar, MA; Mohammad, QD; Ahmed, S (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):131-5. The abstract of this article is available on the PubMed website